Measurement of the differential inclusive B+ hadron cross sections in pp collisions at root s=13TeV - Khachatryan,V; Sirunyan,AM; Tumasyan,A; Adam,W; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Flechl,M; Friedl,M; et al. (PHYSICS LETTERS B, 2017)
The differential cross sections for inclusive production of hadrons are measured as a function of the transverse momentum and rapidity in pp collisions at a centre-of-mass energy of 13 TeV, using data collected by the CMS experiment that correspond to an integrated luminosity of 48.1 pb−1. The measurement uses the exclusive decay channel , with mesons that decay to a pair of muons. The results show a reasonable agreement with theoretical calculations within the uncertainties.